Imitative Revolutions: Changes in the Media and Journalism in East-Central Europe - Splichal, Slavko (Javnost-The Public, 2001)
The essay examines a decade of changes in the media after the collapse of the socialist system in East-Central Europe. A unique transformation from socialism to capitalism makes traditional middle-range evolutionary theories of modernisation and (post)modern detraditionalisation - inadequate to grasp the substance of the inordinate changes in the (former) Second World. Instead, an attempt is made to apply Gabriel Tarde's theory of imitation based on the triad consisting of innovation, imitation, and opposition. Tarde's theory of imitation as a general law of development seems to offer a valid explanation of these (r)evolutionary changes because it transcends the division between dependency and diffusionist modernisation theories, and identifies communication (technology) as particularly important on both accounts. Several oppositional tendencies in the ECE countries are identified which are, in different degrees, spread throughout the region and reflect the imitative nature of the new systems. The imitative tendencies are clustered in two broader groups: (1) those imitating external environment, primarily Western Europe and the USA, which comprise denationalisation and privatisation, commercialisation, inter- or transnationalisation, and cross-fertilisation; and (2) those imitating the past, i.e. the former system of state socialism: renationalisation, and nationalistic and religious exclusivism.